Mussel‐Inspired Plasmonic Nanohybrids for Light Harvesting. (13th March 2014) - Lee, Minah; Kim, Jong Uk; Lee, Joon Seok; Lee, Byung Il; Shin, Jonghwa; Park, Chan Beum
<x xml:space="preserve">Abstract</x> Core–shell plasmonic nanohybrids are synthesized through a simple solutionbased process utilizing mussel‐inspired polydopamine (PDA). The multi‐purpose PDA not only facilitates plasmonic metal formation, but also serves as a scaffold to incorporate photosensitizers around the metal cores, as well as an adhesive between the nanohybrids and the substrate. The resulting plasmonic assembly exhibits highly enhanced light absorption in photo catalytic systems to augment artificial photosynthesis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>